How Organizational Communications Influence the Satisfaction of The Employees Who Work from Home - Said, Meldasari; Bachtiar, Yanuar; Masdulhak, Khairillah (AIBPM Publisher, 2023)
Working remotely often creates communication barriers that impact effectiveness and cause work frustration. This study aims to study the effect of organizational communications (downward, upward and horizontal) where employees work from home on job satisfaction, with the assumption that good communication can provide job satisfaction. This study also analyzes differences in communication attitudes between management and employees both downward and upward, seen from openness, empathy and supportiveness. Questionnaires were distributed to 100 respondents randomly who work from home (or hybrid), spread across Jakarta city and the suburban towns from various industries. Tests were carried out using multiple regression methods, step test, and sign test to see differences in communication attitudes between downward and upward. The results of the study show that downward, upward and horizontal communication have a partial effect on the job satisfaction of employees who work from home. Furthermore, from the results of the step test analysis it was found that horizontal communication was the biggest contributor to job satisfaction. The results of the sign test indicated that there were differences between downward and upward communication, it can be concluded that upward communication is more open, more empathetic, and more supportive than downward communication.